Perbandingan Kualitas Air Sumur Galian dan Bor Berdasarkan Parameter Kimia dan Parameter Fisika - Indri Lita Lestari; Abdul Rahman Singkam; Fenty Agustin; Pingkan Luthfiyyah Miftahussalimah; Anggie Yovita Maharani; Rusma Lingga (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to analyze and compare the quality of dug well water and bore well water around the UNIB Kandang Limun campus. The descriptive method was used to analyze 60 samples, consisting of 30 water samples for each dug well and drilled well. The parameters measured were the degree of acidity (pH), total dissolved particles (TDS), salt content, and electrical conductivity (DHL). This study found that only 35% of the samples met the class I water quality standards. The samples consisted of 7 dug well samples and 14 drilled well samples. Most of the samples (53%) had an acidic pH below 6.5, while the other 12% did not meet the quality standards from TDS, DHL, or both. The pH value of dug well water was significantly lower (more acidic) than drilled well water (p < 0.0001, F1.58=27.28), but the TDS and DHL values ​​in drilled well water were significantly higher (p < 0.01, F1.58=9.09 for TDS; p < 0.001, F1.58=15.89 for DHL). In conclusion, the water quality of drilled wells in the Kandang Limun Campus area is better than that of dug wells. Keywords: Lemonade Cage, Water Quality, Drilling Well, Excavation Well